A Case Series of Bowen’s Disease Treated with the Combination of Cryosurgery and Ingenol Mebutate and Followed Up with Optical Coherence Tomography - Georgios Gaitanis; Theodora Tsironi; Panagiota Spyridonos; Ioannis D. Bassukas (Case Reports in Dermatological Medicine)
Bowen’s disease (BD) is a relatively rare in situ squamous cell carcinoma (SCC) with a limited potential of becoming invasive. Ingenol mebutate (IM) was relatively successful for the treatment of BD lesions in small case series. Optical coherence tomography (OCT) is a promising method for the diagnosis of cutaneous keratinocytic carcinomas, including BD. Herein we report the treatment of BD with the combination of cryosurgery and IM and the application of OCT imagining in treatment monitoring. Patients treated within a period of 12 months are retrospectively compiled. Treatment consisted of a mild cryosurgery session (liquid N2, open spray, and 2 freeze-thaw cycles of 15 sec each) of a field including the BD lesion and a 0.5cm rim and IM application for 4 consecutive days starting at the cryosurgery day. Four patients (3 females; average age: 76.5 years) with 4 lesions (20-70mm maximal diameter; average 36.2mm) were included. Healing was excellent and no relapse was observed at 12 months’ follow-up. Baseline OCT revealed a disarranged, thickened epidermis, while a normally layered epidermis overlying a hyperreflective dermis was present after treatment. Conclusively, the combination of cryosurgery followed by IM is a feasible, effective treatment for BD that should be evaluated in further studies.